Information Effects of Euro Area Monetary Policy: New evidence from high-frequency futures data - Mark Kerssenfischer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Central bank announcements have strong effects on interest rates, but small or even counterintuitive effects on economic expectations. Based on tick-by-tick futures prices on bonds and stock prices, I confirm these seemingly puzzling results for the euro area and provide evidence that they are due to central bank information effects. That is, ECB announcements convey information not only about monetary policy, but also about economic fundamentals. I separate these "information shocks" from "pure policy shocks" via sign restrictions and find intuitive effects of both shocks on a wide set of financial market prices, survey expectations and macroeconomic aggregates.
Keywords: E52; E44; E32; C32; 330; Monetary Policy; High-Frequency Identification; Central Bank Information